Analysis Narratives of Improving Students' Scientific Literacy Through Socio-Scientific Issues-Based Science Learning in Elementary Schools - Yadi Heryadi; Yuyun Yuningsih; Eman Sulaeman; Dede Kurnia Adiputra; Deby Fauzi Ashidiqi; Dine Trio Ratnasari (Yayasan Adra Karima Hubbi, 2026)
Background. This research is motivated by the low scientific literacy of elementary school students caused by science learning that is still oriented towards memorization and lacks contextualization. Purpose. This study aims to analyze the improvement of students' scientific literacy through the implementation of Socio-Scientific Issues (SSI)-based science learning. Method. This study uses a quantitative approach with a quasi-experimental design and a one-group pretest-posttest design. The subjects of the study were 30 fourth-grade elementary school students. Results. The data collection technique used a science literacy test, while data analysis was carried out using the N-Gain test. The results showed that the average pretest score of 56.3 increased to 82.7 in the posttest, with an N-Gain value of 0.60 which is included in the moderate category. This indicates that SSI-based learning is effective in improving students' scientific literacy, especially in the aspects of conceptual understanding, data interpretation, and evidence-based decision making. Conclusion. Thus, Socio-Scientific Issues-based learning can be an alternative, innovative and contextual learning strategy in improving elementary school students' scientific literacy.